NON â BAYESIAN AND BAYESIAN RELIABILITY ESTIMATION FOR GAMMA STRESS â WEIBULL STRENGTH MODELS - Karam, Nada Sabah; Khnem, AhmedÃ‚Â Husen (MAGISTRA, 2015)
paper deals with the estimation of reliability function (RF) of Gamma strength- Weibullstressa models with different shape and scale parameters. The maximum likelihood, moments, and three bayesestimators using three different prior distributions of RF, are obtained for different and known shape parametersand different and unknown scale parameters. A simulation based on different sample sizes anddifferent parametervalues, is used to study the performance of the reliability estimators.